1999
DOI: 10.1073/pnas.96.21.12198
|View full text |Cite
|
Sign up to set email alerts
|

Pain modulation by release of the endogenous cannabinoid anandamide

Abstract: Synthetic cannabinoids produce behavioral analgesia and suppress pain neurotransmission, raising the possibility that endogenous cannabinoids serve naturally to modulate pain. Here, the development of a sensitive method for measuring cannabinoids by atmospheric pressure-chemical ionization mass spectrometry permitted measurement of the release of the endogenous cannabinoid anandamide in the periaqueductal gray (PAG) by in vivo microdialysis in the rat. Electrical stimulation of the dorsal and lateral PAG produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
278
1
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 445 publications
(300 citation statements)
references
References 59 publications
14
278
1
7
Order By: Relevance
“…Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Prior reports (Burstein et al 1997;Huang et al, 2001), suggest that NAGly might have analgesic properties similar to those reported for anandamide (Pertwee, 2001;Walker et al, 1999) but would be inactive in assays for psychotropic action such as the "ring test (Pertwee, 1972). The latter was in agreement with a report showing a lack of affinity by NAGly for the cannabinoid receptor, CB1 (Sheskin et al, 1997).…”
Section: Lipoamino Acids (Fatty Acid-amino Acid Conjugates): Generalsupporting
confidence: 85%
“…Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Prior reports (Burstein et al 1997;Huang et al, 2001), suggest that NAGly might have analgesic properties similar to those reported for anandamide (Pertwee, 2001;Walker et al, 1999) but would be inactive in assays for psychotropic action such as the "ring test (Pertwee, 1972). The latter was in agreement with a report showing a lack of affinity by NAGly for the cannabinoid receptor, CB1 (Sheskin et al, 1997).…”
Section: Lipoamino Acids (Fatty Acid-amino Acid Conjugates): Generalsupporting
confidence: 85%
“…In addition, group I mGluR activation initiates 2-AG biosynthesis (Jung et al, 2005) and endocannabinoid-mediated synaptic plasticity in several other brain regions (Ohno-Shosaku et al, 2002;Zhu and Lovinger, 2005;Grueter et al, 2006;Centonze et al, 2007;Uchigashima et al, 2007). In the present study, we have not identified the endocannabinoid involved; however, anandamide and 2-AG are potential candidates, because they are both produced within the PAG under certain conditions (Walker et al, 1999;Hohmann et al, 2005).…”
Section: Glutamate Spillover Drives Endocannabinoid Signalingmentioning
confidence: 53%
“…Later work revealed the role of endogenous ligands by demonstrating mobilisation of AEA (108) , and CB 1 -mediated antinociception, following either electrical stimulation of these regions or a peripheral administration of formalin (109) . Enhancing AEA signalling in these areas via inhibition of FAAH activity is anti-nociceptive in acute pain (110) , probably via disinhibition of descending inhibitory inputs from the brainstem to the spinal cord, inhibiting spinal nociceptive signalling (for a review of the pathways involved, see (38)(39)(40) ).…”
Section: Supra-spinal Mechanismsmentioning
confidence: 99%